2020
DOI: 10.3390/cancers12092636
|View full text |Cite
|
Sign up to set email alerts
|

Trial Sponsorship and Time to Reporting for Phase 3 Randomized Cancer Clinical Trials

Abstract: The pace of clinical trial data generation and publication is an area of interest within clinical oncology; however, little is known about the dynamics and covariates of time to reporting (TTR) of trial results. To assess these, ClinicalTrials.gov was queried for phase three clinical trials for patients with metastatic solid tumors, and the factors associated with TTR from enrollment completion to publication were analyzed. Based on the 319 included trials, cooperative-group-sponsored trials were reported at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It is important to note that this study does not suggest that there are inherent differences between the research of for‐profit and nonprofit funding sources, and for‐profit sources are important vehicles for innovation. The above findings do, however, raise questions about the influence of funding sources in oncology research and how anticipated revenue streams may impact the types of trials conducted as well as their design, accrual, reporting, and outcomes 14–20 ,. 33‐40 In recent years, the majority of phase 3 trials have been funded by industry 14,41,42 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is important to note that this study does not suggest that there are inherent differences between the research of for‐profit and nonprofit funding sources, and for‐profit sources are important vehicles for innovation. The above findings do, however, raise questions about the influence of funding sources in oncology research and how anticipated revenue streams may impact the types of trials conducted as well as their design, accrual, reporting, and outcomes 14–20 ,. 33‐40 In recent years, the majority of phase 3 trials have been funded by industry 14,41,42 .…”
Section: Discussionmentioning
confidence: 93%
“…Notably, the study aim was to evaluate the trends of completed, published late‐phase trials that are currently impacting contemporary clinical practice. As such, this study does not directly address the interesting, but separate, question of how therapeutic modality relates to current phase 3 trial design, as the timeline from conception of a phase 3 trial to publication is heterogenous and may systematically differ based on the trial sponsor and trial modality; moreover, recent data demonstrate that one in 15 completed oncology randomized controlled trials are not published 17,47 . Trials published after the data collection date were not included in the study, and the study findings must be interpreted with this in mind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Industry trials may thus have competitive advantages in quality and timeliness. 13,14 Nevertheless, what is less recognized is the high penetration of industry authors and analysts in industry-funded trials. Previous work had suggested that there was a high rate of ghost authorship in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Industry mobilizes resources, expertise, and infrastructure for clinical trials, while public funding is limited . Industry trials may thus have competitive advantages in quality and timeliness . Nevertheless, what is less recognized is the high penetration of industry authors and analysts in industry-funded trials.…”
Section: Discussionmentioning
confidence: 99%